PENGARUH PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM - Gf Gustina Siregar; Tetty Junita Purba; Stefani Anatasya; Ribka Ayu Putri Gulo (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Oxytocin massage is massage along the spine (vertebrae) and is an attempt to stimulate the hormone oxytocin after childbirth. The purpose of this study was to analyze the Effect of Oxytocin Massage on Increasing Breast Milk Production in Menta Clinic, Jalan Patumbak Pasar V Market, Deli Serdang Regency in 2019. The research method used was a quasi-experimental research method (Quasi experiment) with a case control group pretest and posttest design. This research was conducted at the Menta Clinic from April to June 2019 with a total sample of 20 mothers with the provision of 10 mothers in the control group and 10 mothers in the intervention group. From the results of statistical tests conducted using the chi-square test, the value of p = 0.007 (p <α) was obtained where 0.007 <0.05, which means that there is a significant influence between Oxytocin Massage on increasing milk production in Postpartum Mothers. Postpartum mothers are expected to do oxytocin massage in order to increase milk production in women whose milk production is low.